Estado del arte de brocas de perforación (2011)
This paper presents a compilation of the basics of the components of the drill bit, also describes the different types of drills, fundamental characteristics, cutting characteristics, Types of Building Materials, and other types of cutters and performs a brief summary of new technologies published in the area of design and selection of drill bits.